2014
DOI: 10.1017/s1751731114000779
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of porcine receptors for enterotoxigenic Escherichia coli with fimbriae F4ad and their relation to other F4 receptors

Abstract: Enteric Escherichia coli infections are a highly relevant cause of disease and death in young pigs. Breeding genetically resistant pigs is an economical and sustainable method of prevention. Resistant pigs are protected against colonization of the intestine through the absence of receptors for the bacterial fimbriae, which mediate adhesion to the intestinal surface. The present work aimed at elucidation of the mode of inheritance of the F4ad receptor which according to former investigations appeared quite conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Some of the additional mucin receptors might represent released degradation products of larger brush border receptors. Depending on the presence or absence of the different F4 receptors, up to 8 groups of receptor phenotypes were described (157), with six having been studied in more details (158)(Table 5). As shown with different glycoconjugate receptors, the three F4 variants demonstrate lectin activities specific for a minimal recognition sequence containing a ß-linked HexNAc, a terminal ß-linked galactose enhancing the binding (159).…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…Some of the additional mucin receptors might represent released degradation products of larger brush border receptors. Depending on the presence or absence of the different F4 receptors, up to 8 groups of receptor phenotypes were described (157), with six having been studied in more details (158)(Table 5). As shown with different glycoconjugate receptors, the three F4 variants demonstrate lectin activities specific for a minimal recognition sequence containing a ß-linked HexNAc, a terminal ß-linked galactose enhancing the binding (159).…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…However, Goetstouwers et al (2014) rejected that hypothesis. Rampoldi et al (2014) examined four different small intestinal sites instead of one for adhesion of the fimbrial variants but did not find any relations to the strong receptors for variants F4ab and F4ac. Previous studies on RT-PCR analysis reported that the porcine MUC13 mRNA expression was markedly different in diverse tissues, with the highest level in the jejunum; moderate levels in the trachea, stomach and liver; and low levels (or no expression) in the other 14 tissues (Zhang et al 2008).…”
Section: Jejunal Expression Of Muc 13 Mrnamentioning
confidence: 92%
“…Targeted mating allowed for the discrimination between fully adhesive receptors (F4abR FA and F4adR FA ), expressed on all enterocytes and at all sites in the small intestine, and partially adhesive receptors (F4abR PA and F4adR PA ), variably expressed at different sites, often leading to partial bacterial adhesion (Rampoldi et al . ). These observations led to three additional receptor phenotypes: A2 (F4abR FA /F4acR + /F4adR PA ), C2 (F4abR PA /F4acR − /F4adR PA ) and D2 (F4abR − /F4acR − /F4adR PA ).…”
Section: Introductionmentioning
confidence: 97%
“…The genes encoding the F4 receptors have not yet been identified (Rampoldi et al . , ). Three antigenic variants of F4 have been described: F4ab, F4ac and F4ad (Guinee & Jansen ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation